Advances in some hypersonic vehicles technologies - Agarwal, Ramesh K. 1947- (InTech, 2018)
The book describes the recent progress in some hypersonic technologies such as the aerodynamic modeling and numerical simulations of rarefied flows, boundary layer receptivity, coupled aerodynamics, and heat transfer problems, including fluid-thermal-structure interactions and launcher aerodynamic design as well as other miscellaneous topics, such as porous ceramic composite phase change control system and vehicle profile, following LQR design. Both the researchers and the students should find the material useful in their work.
Keywords: Überschallflugzeug